The oak forest of the Dendropark “Оlexandria”. Part 2. Models of forest decline - Nina Dragan; Nataliia Boiko; Nataliia Doiko; Oleksandr Sylenko; Yuriy Pydorich (Інтродукція Рослин)
The results of new studies of the old natural forest of the “Оlexandria” State Dendrological Park of the National Academy of Science of Ukraine are presented. Complexes of negative factors in different forest areas caused different degradation models. Episodic decline in the 1980s due to abnormal climatic conditions and defoliation of oaks by xylophages are explained by Thomas’s model of decline with further interference with Macháčová’s model of decline. Without weather anomalies, the decline followed Houston’s model on a significant part of the timber for a long time. It was a linear process in which healthy trees weakened due to random negative factors and died as a result of the subsequent action of secondary pathogens. Most of the forest declined over a long time, according to Manion’s model. The initiating factor of decline was artificial, caused by anthropogenic pollution in the western part of the forest and interference with the integrity and structure in the central part. The latter was the most harmful for the forest, and it caused a strong ecotonization of the forest with a massive loss of oaks in the ecotones. The destruction of timber due to anthropogenic intervention was linear and irreversible. Under the action of factors of a non-anthropogenic nature, the destruction of the forest could be suspended if the action of adverse factors could be terminated. The modern aridization of the climate caused a significant deterioration of the oak forest, increased the loss of oak trees, and varied the patterns of decline in its anthropogenically transformed areas.